Pengaruh Pelatihan terhadap Kinerja Pegawai pada Puskesmas Simpang Kawat Kota Jambi - M Alhudhori (Universitas Batanghari Jambi, 2018)
This research entitled Training Effect Against Employee Performance Of Simpang Kawat Health Center In Jambi City . Objectives of this research are to know the training activity, and performance of the Employee. Survei was used as method of this research. The data was collected by using quetioner. For analizing data, verificative method was used to proof that training influence upon performance of the employee. Influence of training upon the employee performance were analized by means of simply regression. The result of this research shows that according to the employee training activity and performance of the Simpang Kawat Health Center were good. Moreover, training have influence significantly upon the employee performance.